GMJ 2020
DOI: 10.31661/gmj.v9i0.1781
|View full text |Cite
|
Sign up to set email alerts
|

Association study of the beta-adrenergic receptor genetic variant Gly389Arg and fluoxetine response in major depression

Abstract: Background: Pharmacogenetics has proven role in the treatment of different illnesses. Patients with special genotypes may achieve a better response to a specific drug. On the other hand, genetic parameters markedly contribute to the development of major depressive disorder (MDD). The significance of adrenergic system compartments in cognition and behavior, and their role in etiology of depression denote that adrenergic receptors beta gene polymorphism(s) might also have an association with drug response. Thus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…A clinical study discerned the influence of the G1165C polymorphism in the beta-1 adrenoceptor gene on individual differences in response to sertraline, and it was found that CC genotype-carrying individuals responded five times more to sertraline compared to other variants and that the C allele carriers responded three times more to sertraline than patients with the G allele [ 63 ]. Interestingly, the antidepressant-promoting effect of polymorphism in the beta-1 adrenoceptor gene was not observed in patients who received repeated treatment with fluoxetine, one of the most frequently prescribed antidepressants [ 64 ]. Moreover, the antidepressant-induced down-regulation of CNS beta-1 adrenoceptors in rodents was in a time course that paralleled the onset of antidepressant action in patients with MDD [ 65 ].…”
Section: Functional Role Of Beta-adrenergic Receptors In Depression A...mentioning
confidence: 99%
“…A clinical study discerned the influence of the G1165C polymorphism in the beta-1 adrenoceptor gene on individual differences in response to sertraline, and it was found that CC genotype-carrying individuals responded five times more to sertraline compared to other variants and that the C allele carriers responded three times more to sertraline than patients with the G allele [ 63 ]. Interestingly, the antidepressant-promoting effect of polymorphism in the beta-1 adrenoceptor gene was not observed in patients who received repeated treatment with fluoxetine, one of the most frequently prescribed antidepressants [ 64 ]. Moreover, the antidepressant-induced down-regulation of CNS beta-1 adrenoceptors in rodents was in a time course that paralleled the onset of antidepressant action in patients with MDD [ 65 ].…”
Section: Functional Role Of Beta-adrenergic Receptors In Depression A...mentioning
confidence: 99%